A Pre Post-COVID-19 Pandemic Review of Regional Connectivity and Socio-Economic Development Reforms: What Can Be Learned by Central and Eastern European Countries from the China-Pakistan Economic Corridor - Atta Ullah; Chen Pinglu; Saif Ullah; Muhammad Ather Elahi (Comparative Economic Research. Central and Eastern Europe, 2021)
This paper aims tohighlight the role of mutual assistance of China and Pakistan's regional connectivity through the China-Pakistan Economic Corridor (CPEC) and show what lessons can be learned by Central and Eastern European Countries (CEECs). CPEC promotes trade, FDI, peace, and sustainable socio-economic development, and it can help to alleviate the effects of COVID-19 inthe region topromote socio-economic development. In this study, we employed the Rolling Window Approach (Rolling Moving Average Approach) for data analysis of pre- and post-COVID-19. It also focuses on before and after the CPEC initiative's impact on the Pakistani economy through the Rolling Window Approach and graphical trends. In Pakistan, thanks to CPEC; trade, FDI, remittance, and the stock exchange (PSX) showed anupward shift. Terrorism decreased, which indicates apositive sign for peace and socio-economic development. However, currency depreciation increased, and the exchange rate trend is going up against the dollar, hurting the economy badly inseveral ways, such as the balance of payment, current account deficit, and lower some exports. To mitigate these issues, Pakistan and China have taken steps astrade for mulated indomestic cur-rency between China and Pakistan. During COVID-19, the provision ofhealth care equipment onapriority basis from China helped tocombat the COVID-19 effects and stabilize Pakistan's Economy. CPEC isstructured toconnect regional economic zones by forming local, regional, and global value chains. To cope with the COVID-19 impacts, socio-economic reforms and regional cooperation are suggested for CEECs with a pre-post circumstances review. Regional integration and cooperation are key to coping with this pandemic. CEECs can learn lessons from CPEC for socio-economic development, reducing violence, and improving the economy.
Keywords: P25; P48; R11; F36; F63; 330; China-Pakistan Economic Corridor (CPEC); exchange rate; FDI; violence; technology; socio-economic development; COVID-19 pandemic